The City That Was: A Requiem of Old San Francisco - Irwin, Will, 1873-1948 (Salt Lake City, UT : Project Gutenberg, 2002)
"The City That Was: A Requiem of Old San Francisco" by Will Irwin is a historical account written in the early 20th century, shortly after the devastating 1906 earthquake that destroyed much of San Francisco. The book reflects on the vibrant culture and unique atmosphere of the city that once thrived before this tragic event, capturing its essence and the profound impact of its loss. In the narrative, Irwin mournfully recounts the charm of old San Francisco, describing its picturesque hills, diverse population, and the lively, romantic spirit that permeated its streets. He paints a vivid picture of the city's architecture, which included quirky, informal structures reflecting the eclectic nature of its inhabitants. Irwin captures the city's dynamic social scene, from the bustling Barbary Coast to the lively restaurants where diverse culinary traditions flourished. The book serves not only as a requiem for what was lost but also as a testament to the resilience of a unique city, leaving readers with a deep sense of nostalgia for the rich life and culture that defined old San Francisco before it was irrevocably changed. (This is an automatically generated summary.)
Release date is 2002-07-01
Produced by David A. Schwan, and David Widger
Keywords: San Francisco (Calif.) -- Description and travel; San Francisco (Calif.) -- History; San Francisco (Calif.) -- Social life and customs